Investigations of the Nucleating Agent Effects on Polypropylene of Pumice from Three Distinct Areas in Türkiye - Ozdemir, Yasin; Atagur, Metehan; Sen, Ibrahim; Sever, Kutlay (Mdpi, 2025)
This study investigates the mechanical and thermal properties of polypropylene (PP) composites incorporating pumice, a naturally occurring porous volcanic rock with high SiO2 content, sourced from three regions in T & uuml;rkiye (Nev & scedil;ehir, Ala & ccedil;at & imath;, and K & uuml;tahya). Pumice was processed to particle sizes below 10 microns to maximize nucleating effectiveness, and composites were fabricated by melt compounding. The distinct mineralogical composition, porosity, and surface chemistry of the pumice samples enabled systematic evaluation of how regional variations influence crystallization and mechanical performance. A multi-analytical characterization approach, including thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), and standardized mechanical tests (tensile, flexural, and impact), was applied. Results revealed that Ala & ccedil;at & imath; pumice at 0.1 wt% increased the impact strength of PP by about 11%, while maintaining stiffness. This demonstrates that pumice, unlike conventional fillers, can simultaneously enhance toughness and rigidity. Thermal analysis confirmed improved stability, with higher degradation onset and maximum decomposition temperatures observed in pumice-filled PP. DSC results indicated that certain pumice loadings promoted nucleation and increased crystallinity, while excessive amounts disrupted chain packing. SEM examinations confirmed uniform dispersion at low loadings, with agglomeration at higher levels reducing impact resistance. This work provides the first systematic demonstration of pumice powders as effective nucleating agents in PP, combining regional mineralogical diversity with measurable performance benefits. These findings indicate that pumice can serve as a sustainable, low-cost alternative to conventional nucleating agents, with potential applications in polymer components requiring improved toughness and thermal stability.
Keywords: pumice; nucleating agent; polypropylene (PP)